A review on tetracycline removal from aqueous systems by advanced treatment techniques. Issue 45 (21st July 2020) - Gopal, Geetha; Alex, Sruthi Ann; Chandrasekaran, N.; Mukherjee, Amitava
Abstract : Tetracycline occurrence and advanced treatment techniques. Abstract : Tetracycline (TC), a frequently used drug for human and veterinary therapeutics, is among the most common antibiotic residues found in nature. Lack of advanced treatment techniques in the wastewater treatment plants (WWTPs) to remove residual TC from domestic and hospital wastewater poses a serious environmental risk. It is important to have an insight into the different advanced treatment techniques for efficient removal of TC from the surface water and in the WWTPs. The aim of this review is to discuss the nature and occurrence of TC in surface water and to present an overview of the various advanced treatment techniques for TC removal. The advanced treatment techniques include advanced oxidation processes (photolysis, ozonation, and catalytic/UV light-based degradation), membrane filtration, reverse osmosis, and adsorption techniques. Adsorption and integrated oxidation treatment techniques are the most widely studied methods, and they are widely accepted because of less cost, reusability, and toxic-free nature. Further, the uses of various types of catalysts for photodegradation and various sorbents for adsorption of TC are also presented. Finally, the importance of green nanocomposite for environmental sustainability in TC removal is emphasized.